2002
DOI: 10.1002/nur.10022
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with conjugated linoleic acid does not improve nutritional status of tumor‐bearing rats*

Abstract: Tumor necrosis factor-alpha (TNF) is an immunoregulatory cytokine that plays a major role in tumor-induced anorexia and weight loss. Conjugated linoleic acids (CLA) are naturally occurring isomers of linoleic acid that, when added to the diet, improve food intake and body weight in mice injected with TNF. The purpose of the present study was to examine the effects of a diet supplemented with 0.5% CLA on the nutritional status of rats implanted with the Morris 7777 hepatoma. Body weight, food intake, serum leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
3
4
0
Order By: Relevance
“…In the present study, CLA did not affect growth of the colon-26 adenocarcinoma in mice. Similar findings were observed in mice inoculated with mammary tumors (Wong et al, 1997) and rats inoculated with the Morris 7777 hepatoma (McCarthy-Beckett, 2002). While it is unclear whether a diet enriched with CLA might slow tumor growth, the data from the present study suggest that the anti-cachectic effects of CLA in mice bearing the colon-26 adenocarcinoma were not secondary to suppressed tumor growth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, CLA did not affect growth of the colon-26 adenocarcinoma in mice. Similar findings were observed in mice inoculated with mammary tumors (Wong et al, 1997) and rats inoculated with the Morris 7777 hepatoma (McCarthy-Beckett, 2002). While it is unclear whether a diet enriched with CLA might slow tumor growth, the data from the present study suggest that the anti-cachectic effects of CLA in mice bearing the colon-26 adenocarcinoma were not secondary to suppressed tumor growth.…”
Section: Discussionsupporting
confidence: 89%
“…It is also possible that muscles of the tumor-bearing mice were more susceptible to the metabolic effects of CLA than muscles of healthy control animals. In contrast, .5% CLA given in the diet of male rats inoculated with the Morris 7777 hepatoma had no effect on total body protein compared to animals given the control diet and there was no effect of CLA on levels of TNF secreted by splenocytes stimulated ex vivo with LPS (McCarthy-Beckett, 2002). Others have noted that CLA has a greater effect on body fat and serum TNF in mice than in rats (Akahoshi et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
“…These data suggest that metabolism of AA does not play a major role in the development of SMW in mice bearing the B16 melanoma. These data are supported by others who found that .5% CLA in the diet had no effect on body weight loss in rats bearing the Morris 7777 hepatoma (McCarthy-Beckett, 2002), a tumor cell line that increased both TNFa and IL-6 in spleen cells of tumor-bearing animals (Murray, Schell, McCarthy, & Albertini, 1997). Similarly, others found that a diet containing 1.0% CLA did not improve body weight in mice bearing a mammary carcinoma (Wong et al, 1997).…”
Section: Discussionsupporting
confidence: 51%
“…McCarthy and Graves and McCarthy‐Beckett et al . reported that 0.5% of CLA in the diet preserved muscle mass in mice with Lewis Lung carcinoma, but had no effect in mice with B16 melanoma or in rats with Morris 7777 hepatoma 26, 45. Wong et al .…”
Section: Discussionmentioning
confidence: 99%